2017
DOI: 10.1039/c6ra17236a
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of zinc sulfide quantum dots using waste off-gas from a metal bioremediation process

Abstract: Dissimilatory reduction of sulfate, mediated by various species of sulfate-reducing bacteria (SRB) and a few characterized species of archaea, can be used to remediate acid mine drainage (AMD). Hydrogen sulfide (H 2 S/HS À ) generated by SRB removes toxic metals from AMD as sulfide biominerals. For this, SRB are usually housed in separate reactor vessels to those where metal sulfides are generated; H 2 S is delivered to AMD-containing vessels in solution or as a gas, allowing controlled separation of metal pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…In this system, the sulfide generated can be partially re-oxidized to elemental sulfur by using sulfide-oxidizing bacteria, while the solid product is removed and applied as fertilizer [24]. However, relatively little is known about the synthesis of metallic nanoparticles using biogenic H 2 S. The synthesis of nanoparticles of ZnS from a sulfate solution was recently reported by feeding biogenic H 2 S from the off-gas generated from a sulfidogenic metal remediation process [3]. The present study examined whether the H 2 S produced from this low-pH sulfidogenic reactor, set up for the removal of copper and sulfate from an acidic mine water, can be used to fabricate CuS nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this system, the sulfide generated can be partially re-oxidized to elemental sulfur by using sulfide-oxidizing bacteria, while the solid product is removed and applied as fertilizer [24]. However, relatively little is known about the synthesis of metallic nanoparticles using biogenic H 2 S. The synthesis of nanoparticles of ZnS from a sulfate solution was recently reported by feeding biogenic H 2 S from the off-gas generated from a sulfidogenic metal remediation process [3]. The present study examined whether the H 2 S produced from this low-pH sulfidogenic reactor, set up for the removal of copper and sulfate from an acidic mine water, can be used to fabricate CuS nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…The H 2 S produced by the low-pH sulfidogenic bioreactor was removed in a stream of OFN with a flow rate of 150 mL·min −1 extracting 0.1% (v/v) H 2 S. The gas stream was fed into 100 mL serum bottles containing 100 mL of 2 mM CuSO 4 in 50 mM of citrate buffer (pH 6.0), which were subsequently sealed, and head space air was displaced by passing nitrogen through the solution [3]. The copper solutions were sparged by this gas stream for 5, 15, 30, 45, and 60 min, with shaking between dosing, and then stored in the dark at 4 • C for characterization of the nanoparticles.…”
Section: Formation Of Copper Sulfide Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…A first report [60] showed that the characteristics and the light emitting properties of ZnS quantum dots made by use of bacterially made waste H 2 S left over from the metal bioremediation process [50,51] were comparable to those made by "classical" methods, which required more complex procedures. As a potential synthesis method at scale, this shows potential for commercial QD production and introduces the possibility to use these biogenic ZnS QDs to promote algal growth for the applications described above and also to provide algal feedstock as a nutrient source for other processes (e.g.…”
Section: Potential Alternative Strategy For Economic Production Of Qumentioning
confidence: 99%